Economic evaluation and user perspective of urban forest benefits in Kuala Lumpur and Putrajaya, Malaysia - Abdul Aziz, Izza Shazleen (2016)
The infill of the residential areas around Kuala Lumpur and Putrajaya have the potential to cause changes in the quantity and quality of urban forest for dwellers need and limited numbers of studies had been done to identify the changes effect on users who reside within these areas. Development projects to fulfill the need of condensing dwellers usually causing loss of amenity values of the urban forest, which can affect the users or surround. Nowadays, urban dwellers are less attracted to visits and socializing at the urban forest areas provided by the local authority and developers because of the unattractiveness or the similarity of the area to human-made others urban forest. This may cause fewer users in the area, thus might have given a chance to developers or officials to use some part of the area for other more beneficial development. Urban forests are important in creating recreational opportunities to maintain a high-quality urban environment. Besides being seen as a place for recreational opportunities, it also has wide benefits from economic to environmental aspect. By evaluating the economic value of existing natural urban forest from the user’s perspective, the percentage of the urban forest spaces been threatened by the development might be lowered, and authorities or other private sectors will think twice before using the urban forest area for other development and projects.This study discusses the willingness to pay of users in evaluating urban forest benefits and presents the main results of an empirical study conducted in two study sites, each respectively in Kuala Lumpur and Putrajaya, Malaysia. This study used face to face surveys of 500 urban respondents, 250 respondents for each study sites who are aged 15 and older. Respondents then were asked to answers the questionnaire related to their willingness to pay for the benefits of urban green spaces. The results suggest that most visitors were willing to pay for the use of wellmaintained and planned recreation areas. Furthermore, approximately half of the respondents were prepared to pay for the entrance fees suggested for each study sites. The results can be used to assess the probability of the management of urban forests. Also, the results are useful in determining the value of green space benefits in different land use options.